Mekanisme Dampak Pemanasan Global Oleh Gas Rumah Kaca - Seftiani, Mustika Ayu; Sudarti, Sudarti; Yushardi, Yushardi (Jurnal Pendidikan, Sains Dan Teknologi, 2024)
The article titled "Mechanism of the Effects of Global Warming by Greenhouse Gases" explores the impact of greenhouse gases on global warming. It emphasizes the role of human activities in climate change and the need to reduce anthropogenic CO2 emissions to mitigate its effects. The study adopts qualitative research methods, collecting data through observation, questionnaires, and interviews. The questionnaire assesses public awareness, knowledge, attitudes, and behaviors towards global warming and greenhouse gases. Findings reveal inadequate attention and limited application of knowledge in daily lives, with excessive use of fossil fuels and private vehicles contributing to the deterioration of the atmosphere. Global warming, caused by human activities and greenhouse gas emissions like methane, carbon dioxide, and nitrous oxide, poses significant environmental challenges, affecting temperature rise and climate patterns. While global warming can have some positive impacts on agricultural productivity and biodiversity in colder regions, the overall negative impacts outweigh the positive ones. The article underscores the importance of understanding greenhouse gas dynamics and calls for collective action to address the issue.